International Survey to Establish Prioritized Outcomes for Trials in People With Coronavirus Disease 2019. Issue 11 (November 2020) - Evangelidis, Nicole; Tong, Allison; Howell, Martin; Teixeira-Pinto, Armando; Elliott, Julian H.; Azevedo, Luciano Cesar; Bersten, Andrew; Cervantes, Lilia; Chew, Derek P.; Crowe, Sally; Douglas, Ivor S.; Flemyng, Ella; et al.
Abstract : Objectives: There are over 4, 000 trials conducted in people with coronavirus disease 2019. However, the variability of outcomes and the omission of patient-centered outcomes may diminish the impact of these trials on decision-making. The aim of this study was to generate a consensus-based, prioritized list of outcomes for coronavirus disease 2019 trials. Design: In an online survey conducted in English, Chinese, Italian, Portuguese, and Spanish languages, adults with coronavirus disease 2019, their family members, health professionals, and the general public rated the importance of outcomes using a 9-point Likert scale (7–9, critical importance) and completed a Best-Worst Scale to estimate relative importance. Participant comments were analyzed thematically. Setting: International. Subjects: Adults 18 years old and over with confirmed or suspected coronavirus disease 2019, their family members, members of the general public, and health professionals (including clinicians, policy makers, regulators, funders, and researchers). Interventions: None. Measurements: None. Main Results: In total, 9, 289 participants from 111 countries (776 people with coronavirus disease 2019 or family members, 4, 882 health professionals, and 3, 631 members of the public) completed the survey. The four outcomes of highest priority for all three groups were: mortality, respiratory failure, pneumonia, and organ failure. Lung function, lung scarring, sepsis, shortness of breath, and oxygen level in the blood were common to the top 10 outcomes across all three groups (mean > 7.5, median ≥ 8, and > 70% of respondents rated the outcome as critically important). Patients/family members rated fatigue, anxiety, chest pain, muscle pain, gastrointestinal problems, and cardiovascular disease higher than health professionals. Four themes underpinned prioritization: fear of life-threatening, debilitating, and permanent consequences; addressing knowledge gaps; enabling preparedness and planning; and tolerable or infrequent outcomes. Conclusions: Life-threatening respiratory and other organ outcomes were consistently highly prioritized by all stakeholder groups. Patients/family members gave higher priority to many patient-reported outcomes compared with health professionals. Abstract : Supplemental Digital Content is available in the text.